The Origins of Mental Toughness – Prosocial Behavior and Low Internalizing and Externalizing Problems at Age 5 Predict Higher Mental Toughness Scores at Age 14 - Sadeghi Bahmani, Dena; Hatzinger, Martin; Gerber, Markus; Lemola, Sakari; Clough, Peter J.; Perren, Sonja; von Klitzing, Kay; von Wyl, Agnes; Holsboer-Trachsler, Edith; Brand, Serge (Frontiers in Psychology, 2016)
Background: The concept of mental toughness has gained increasing importance among groups other than elite athletes by virtue of its psychological importance and explanatory power for a broad range of health-related behaviors. However, no study has focused so far on the psychological origins of mental toughness. Therefore, the aims of the present study were: to explore, to what extent the psychological profiles of preschoolers aged five were associated with both 1) mental toughness scores and 2) sleep disturbances at age 14, and 3) to explore possible gender differences. Method: Nine years after their first assessment at age five (preschoolers), a total of 77 adolescents (mean age: 14.35 years; SD = 1.22; 42% females) took part in this follow-up study. At baseline, both parents and teachers completed the Strengths and Difficulties Questionnaire (SDQ), covering internalizing and externalizing problems, hyperactivity, negative peer relationships, and prosocial behavior. At follow-up, participants completed a booklet of questionnaires covering socio-demographic data, mental toughness, and sleep disturbances. Results: Higher prosocial behavior, lower negative peer relationships, and lower internalizing and externalizing problems at age five, as rated by parents and teachers, were associated with self-reported higher mental toughness and lower sleep disturbances at age 14. At age 14, and relative to males, females had lower MT scores and reported more sleep disturbances. Results: Higher prosocial behavior, lower negative peer relationships, and lower internalizing and externalizing problems at age five, as rated by parents and teachers, predicted self-reported higher mental toughness and lower sleep disturbances at age 14. At age 14, and relative to males, females had lower MT scores and reported more sleep disturbance. Conclusions: The pattern of results suggests that mental toughness traits during adolescence may have their origins in the pre-school years.